2019
DOI: 10.1038/s41598-019-56509-5
|View full text |Cite
|
Sign up to set email alerts
|

Deep sequencing and automated histochemistry of human tissue slice cultures improve their usability as preclinical model for cancer research

Abstract: Cancer research requires models closely resembling the tumor in the patient. Human tissue cultures can overcome interspecies limitations of animal models or the loss of tissue architecture in in vitro models. However, analysis of tissue slices is often limited to histology. Here, we demonstrate that slices are also suitable for whole transcriptome sequencing and present a method for automated histochemistry of whole slices. Tumor and peritumoral tissue from a patient with glioblastoma was processed to slice cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…However, it is also clear that with rat model alone cannot recapitulate all the features of bone cancer pain in humans, and the species differences in DEGs between rodents and humans is inevitable. As the development processes of primate nervous system are conserved across mammals ( Bakken et al, 2015 ), future studies better employ primate model or by using human tissue slice culture to improve the usability as preclinical model for bone cancer pain research ( Haehnel et al, 2019 ). In addition, studies have also reported the difference in pain mechanisms between males and females, thus, the findings in our current study in females need to be further investigated in males with other cancer cells probably unnecessary the female-specific breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also clear that with rat model alone cannot recapitulate all the features of bone cancer pain in humans, and the species differences in DEGs between rodents and humans is inevitable. As the development processes of primate nervous system are conserved across mammals ( Bakken et al, 2015 ), future studies better employ primate model or by using human tissue slice culture to improve the usability as preclinical model for bone cancer pain research ( Haehnel et al, 2019 ). In addition, studies have also reported the difference in pain mechanisms between males and females, thus, the findings in our current study in females need to be further investigated in males with other cancer cells probably unnecessary the female-specific breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding the extensive characterization of the transcriptome and proteome of the peritumoral area [ 61 , 62 , 63 , 64 , 65 , 66 ], little is known about the expression and involvement of miRNAs in this area and, more specifically, their role in the cross-talk between GBM and microglial cells. One of the first studies on the involvement of miRNAs in the pathogenesis of GBM was conducted by comparing their expression between the central tumor area, surgically and histopathologically recognized as frankly tumoral, and the peripheral glial area, without any evidence of tumor presence, by a surgeon’s macroscopical evaluation [ 39 ].…”
Section: Reviewmentioning
confidence: 99%
“…Also, artificial 2D or 3D matrices poorly mimic the in vivo situation, which consists, in addition to the ECM, of multiple cell types that are capable of influencing and interacting with tumor cells, and thus substantially affect their invasive potential [ 8 ]. Aiming at systems that provide an organotypic microenvironment with its required cellular complexity [ 9 , 10 ], more recent studies have developed tissue slice models in an air-liquid interface setting [ 11 , 12 , 13 , 14 ]. This also included tissue slice co-culture models.…”
Section: Introductionmentioning
confidence: 99%